2016
DOI: 10.1166/jnn.2016.11057
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Nonstick Replica Mold for Transfer Printing of Ag Ink

Abstract: We report the fabrication of flexible replica molds for transfer printing of Ag ink on a rigid glass substrate. As mold precursors, acrylic mixtures were prepared from silsesquioxane-based materials, silicone acrylate, poly(propylene glycol) diacrylate, 3,3,4,4,5,5,6,6,7,7,8,8, 9,9,10,10,10-heptadecafluorodecyl methacrylate, and photoinitiator. By using these materials, the replica molds were fabricated from a silicon master onto a flexible substrate by means of UV-assisted molding process at room temperature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…1. There are 3 main steps of the process; [1] The flexible intermediate molds of the groove structures called line & space (L/S) were prepared by thermal nanoimprint using the aluminum master molds (Type1: width/height/pitch = 500/100/1,000 μm/μm/μm and Type2: width/height/pitch = 50/50/250 μm/μm/μm). The intermediate mold materials used are the cyclic olefin copolymer COC (Polyplastics Co., Ltd., TOPAS 6013-s04) and polyetherimide PEI (Mitsubishi Chemical Co., SUPERIO ○ R UT Type E).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. There are 3 main steps of the process; [1] The flexible intermediate molds of the groove structures called line & space (L/S) were prepared by thermal nanoimprint using the aluminum master molds (Type1: width/height/pitch = 500/100/1,000 μm/μm/μm and Type2: width/height/pitch = 50/50/250 μm/μm/μm). The intermediate mold materials used are the cyclic olefin copolymer COC (Polyplastics Co., Ltd., TOPAS 6013-s04) and polyetherimide PEI (Mitsubishi Chemical Co., SUPERIO ○ R UT Type E).…”
Section: Methodsmentioning
confidence: 99%
“…In the previous research, there was a report on the wiring technique that a replica mold is produced with the silver nano-ink and transferred to the material surfaces. 1,2 In these reports, it has been shown that Ag transferability is improved by controlling the wettability and release ability at the interface between the resin mold and the conductive ink. However, general methods are still focusing on the two-dimensionally of the flat surfaces.…”
Section: Introductionmentioning
confidence: 99%